The Perception of Foreign Staff towards“Khwam Krengjai” in Thai Higher Education Institutions - Orsuwan, Meechai; Hanson, Darren; Malai , Veerapong (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2021)
This qualitative study was part of global collaborative work with the Centre for Leadership and Effectiveness in Organizations (CLEO) at the NEOMA Business School, France. The objective of this research was to uncover the perception of foreign staff towards the concept of “khwam krengjai” through both focus groups and in-depth interviews (semi-structured interview). The 7 key informants had taught at higher education institutions in Thailand. Two interviewees were American, while the other 5 informants were originally from England, China, Taiwan and Malaysia. All participants agreed that the concept of “khwam krengjai” was very complex. However, “khwam krengjai” can be observed through three behaviors that reflected showing respect, avoiding conflict and working styles. Higher Education Institutions should be open and flexible to accept diverse perspectives, behaviors and working styles of their staff, so it benefits the organization in both the short and the long run.